Effects of globalization on food production in five European countries. Issue 5 (24th September 2021) - Khatami, Fahimeh; Ricciardi, Francesca; Cavallo, Angelo; Cantino, Valter
Abstract : Purpose: The purpose of this paper is to investigate the effects of globalization convergence (GC) and its components (social, economic, political, technological and ecological) on food production (FP). Design/methodology/approach: The methodological approach adopted is based on a quantitative approach, using a static panel data analysis with relevant data from five European countries within five time intervals (2013–2017). Findings: The results indicated that three components of globalization (social, technological and ecological) could significantly contribute to the food industry, while two other components of globalization (economic and political) are negatively correlated with FP. Research limitations/implications: This study contributes to the theoretical recognition of the role of globalization in influencing FP in multidisciplinary interactions. Meanwhile, this study's main limitation lies in the statistical method of panel data analysis, since temporal and spatial changes have not been investigated. Originality/value: Despite the literature on globalization's effect on FP, each globalization component's effect has not been investigated appropriately within cross-countries studies. Hence, the present study addresses a gap in the extant literature by examining the globalization effects on the food industry to promote globalized food security, opportunities and solutions in the study areas.